Effect of Microencapsulation by Spray-Drying and Freeze-Drying Technique on the Antioxidant Properties of Blueberry (Vaccinium myrtillus) Juice Polyphenolic Compounds - Wilkowska Agnieszka; Ambroziak Wojciech; Czyżowska Agata; Adamiec Janusz (Polish Journal of Food and Nutrition Sciences, 2016)
Blueberry juice with high polyphenol concentration was spray- or freeze-dried using different coating materials: HP-β-cyclodextrin and β-cyclodextrin. The quality of the obtained powders was characterised by their anthocyanin content, total polyphenols and antioxidant capacity. SEM was used for monitoring structures and size (2–20 μm) of the microparticles. The losses of total phenolic compounds during spray-drying reached 76–78% on average, while these of anthocyanins about 57%. Freeze-dried powders showed better retention values of anthocyanins, which was about 1.5-fold higher than for the spray-dried counterparts. All blueberry preparations studied were characterised by very high radical scavenging activity.